2017
DOI: 10.1680/jgeot.16.p.101
|View full text |Cite
|
Sign up to set email alerts
|

Foundation punch-through in clay with sand: analytical modelling

Abstract: Severe punch-through of jack-up rig foundations can occur due to the presence of a stronger sand layer in a bed of relatively soft clay. Analytical estimation of the bearing capacity and leg load-penetration response on such multi-layer stratigraphies is challenging. Accurate mechanism-based models need to be established in each of the layers involved and the effects of the mechanisms in each of the layers on the response in the other layers must be captured. Based on the recently-developed failure stress-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 28 publications
2
23
0
2
Order By: Relevance
“…The predictive model proposed by Ullah et al [4] has been validated against the centrifuge tests reported by Ullah et al [19] and Hossain [1]. Based on the geometries and soil parameters summarized in Table 1, the peak resistances can mostly be predicted with an error bounded by ±20%, as shown in Figure 2 (solid grey circles) in terms of the ratio r between predicted and measured peak resistances.…”
Section: Modified Predictive Modelmentioning
confidence: 89%
See 3 more Smart Citations
“…The predictive model proposed by Ullah et al [4] has been validated against the centrifuge tests reported by Ullah et al [19] and Hossain [1]. Based on the geometries and soil parameters summarized in Table 1, the peak resistances can mostly be predicted with an error bounded by ±20%, as shown in Figure 2 (solid grey circles) in terms of the ratio r between predicted and measured peak resistances.…”
Section: Modified Predictive Modelmentioning
confidence: 89%
“…The typical penetration resistance profile of spudcan in such deposits is shown in Figure 1, which is presented as the total penetration resistance q versus the penetration depth d measured from the seabed surface to the lowest point of the largest cross-section of spudcan. As the spudcan penetrates in the top clay layer, either a single-layer response (i.e., the penetration response in single-layer clay, without being affected by the underlying layers) or a squeezing response occurs depending on the distance between the spudcan base and the sand layer [1,4,5]. Once the squeezing response is triggered at the depth of d sq , the penetration resistance will increase sharply until reaching the peak value of q peak in the interbedded sand layer at the depth of d peak .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, some studies were reported in this area through physical modelling in a centrifuge (Hossain 2014;Ullah et al 2016a). A comprehensive analytical model was presented in Ullah et al (2016b) for spudcan installation in a clay bed with interbedded sand (i.e. clay-sand-clay) where a method of predicting the complete load-penetration profile was proposed.…”
Section: Introductionmentioning
confidence: 99%